FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN DENGAN GENDER SEBAGAI VARIABEL MODERASI (Studi Pada Perguruan Tinggi di Kota Tegal) - Mohammad Alfian (Monex: Journal of Accounting Research, 2020)
Abstract Universities in Indonesia continue to improve the performance of their institutions by improving the performance of their employees. The performance of higher education institutions is one of the determining factors is the result of employee work. The decline in employee performance from the initial observations can be seen from the increasing number of late hours of the employee being the object of researcher's observation. Based on the results of a literature review conducted by researchers found that it is possible that employee performance is influenced by compensation, work environment and organizational culture. The researcher also guesses that there are differences between men and women on the influence of the compensation environment, work environment and organizational culture on employee performance. Determination of the number of samples in this study using the Slovin formula so as to get a sample of 75 respondents from the employee's morals as many as 276 people and the determination of the sample in this study using random sampling. Researchers in conducting data analysis using the PLS method and using the SmartPLS 2.0 M3 tool. The results of this study found that compensation, work environment and organizational culture affect employee performance without regard to gender, whereas when researchers enter gender it appears that gender successfully moderates the effect of compensation and work environment on employee performance but fails to moderate the effect of organizational culture on employee performance.